Competitividade da cadeia produtiva de carne de frango em Mato Grosso: avaliação dos segmentos de avicultura e processamento - Melz, Laercio Juarez (2010)
Brazil is the second largest producer of chicken meat and the largest exporter. Thanks to an efficient system of coordination chain through contracts, mainly in southern Brazil. Competitiveness is the ability to maintain or enhance participation in markets, internal and external, in a sustained way. Mato Grosso has emerged in poultry production due to its large production capacity of grain, corn and soybeans. The research aimed to identify the determinants of competitiveness of chicken meat from Mato Grosso, with a focus on links in livestock production and slaughter/processing. The methodology uses drivers of competitiveness and assigns evaluations ranging from very unfavorable to very favorable for a number of factors internal to the drivers. The drivers selected were: institutional environment, technology, market structures, governance structures and coordination of the chain, firm management, inputs, storage and transport. A rapid appraisal methodology was used in order to provide information from interviews with selected key players, as well as data from secondary sources. In Mato Grosso, between 2005 and 2008, it was observed an increase of 69.94% in the number of poultry slaughtered in slaughterhouses registered at the Federal Inspection System. The slaughterhouses are located at Várzea Grande and Lucas do Rio Verde, Sadia, at Tangará da Serra and Sorriso, Anhambi, at Nova Mutum, Perdigão, at Mirassol D'Oeste, Frango Bom. The technology used in Lucas do Rio Verde, air-conditioned poultry houses, makes this county the best in terms of feed conversion of the state, between 1.6 and 1.5 kg / kg of chicken. In this county, the scale of production is far superior to the others. Contracts terms used in MT follows the integration model used in southern Brazil. In Nova Mutum, there is an organization representing the class of producers and MT is an association representing the industry, AMAVI. It was concluded that the determinants of competitiveness, to slaughter/processing link are the institutional environment, firm management and storage and transportation; to livestock production link are the institutional environment and market structure. The costs of inputs, especially maize, are cheaper in MT. However, due to the distances of the ports and the lack of other modes, shipping becomes expensive and the flow of production to international markets is impaired.